Validating the Job Stress Scale for Indonesian Police: A CFA Study - Hadiyanti, Karin; Sari, Erita Yuliasesti Diah (Jurnal Psikologi Teori dan Terapan, 2025)
Background: Indonesian adaptation of job stress scale have been tested on teacher samples, re-testing and re-measuring validity and reliability are necessary for use with police samples. Conducting confirmatory factor analysis (CFA) on the Indonesian job stress scale for police samples is critically important because policing is a highly stressful occupation with unique demands not found in teaching professions. Objective: This study aims to measure the validity and reliability of the Indonesian adapted Job Stress Scale for Indonesian police personnel. Method: Using a cross-sectional design, data were collected from a population of 121 Satsamapta officers at Polresta Yogyakarta through accidental sampling, yielding 86 complete responses. CFA evaluated construct validity, while Cronbach’s alpha assessed the reliability of the 13-item Job Stress Scale comprising two factors. Results: Three items (8, 9, and 10) were invalid (factor loading < 0.5). After removal, model fit indices improved significantly (CFI = 0.989, TLI = 0.984, SRMR = 0.0322, RMSEA = 0.0690), and reliability increased to 0.967. Conclusion: The adapted scale, with 10 items, is valid and reliable for measuring work stress among police personnel in Indonesia. This tool can aid further research and interventions to address work stress in law enforcement.   Keywords: Confirmatory factor analysis; job stress scale; police officers; reliability; validity   Abstrak Latar Belakang: Adaptasi job stress scale Indonesia sebelumnya diujikan pada sampel guru, sehingga pengukuran validitas dan reliabilitas ulang diperlukan untuk sampel polisi. Confirmatory factor analysis (CFA) pada skala stres kerja versi Indonesia untuk sampel polisi sangat penting karena pekerjaan kepolisian merupakan profesi yang sangat penuh tekanan dengan tuntutan unik yang tidak ditemukan pada profesi guru. Tujuan: Penelitian ini bertujuan mengukur validitas dan reliabilitas skala stres kerja yang telah diadaptasi untuk personel polisi di Indonesia. Metode: Menggunakan desain cross-sectional, data dikumpulkan dari populasi 121 anggota polisi Satsamapta Polresta Yogyakarta melalui accidental sampling dengan total 86 sampel. Confirmatory Factor Analysis (CFA) mengevaluasi validitas konstruk, sedangkan Cronbach's Alpha mengukur reliabilitas untuk Skala Stres Kerja dengan dua faktor dan total 13 item. Hasil: Terdapat tiga item (8, 9, dan 10) tidak memenuhi kriteria validitas (factor loading < 0.5). Setelah menghilangkan item tersebut, indeks kesesuaian model meningkat signifikan (CFI = 0,989, TLI = 0,984, SRMR = 0,0322, RMSEA = 0,0690), dan reliabilitas meningkat menjadi 0,967. Simpulan: Adaptasi skala stres kerja masih reliabel namun memiliki aitem yang tidak valid. Hasil modifikasi dengan 10 item, dinyatakan valid dan lebih reliabel untuk mengukur stres kerja pada anggota polisi di Indonesia. Implikasi penelitian dapat digunakan untuk peneliti lain dalam mengembangkan alat ukur stres kerja.   Kata kunci: Confirmatory factor analysis; polisi; reliabilitas; skala stres kerja; validitas